Differences in HIV, STI and Other Risk Factors Among Younger and Older Male Sex Workers Who Have Sex With Men in Nairobi, Kenya - Muraguri, Nicholas; Okal, Jerry O.; Temmerman, Marleen; Mukoko, Dunstan; Musyoki, Helgar K.; Gichangi, Peter (Frontiers in Reproductive Health, 2022)
Introduction: Previous surveys of male sex workers (MSW) in sub-Saharan Africa have not fully documented the HIV risks and vulnerabilities by age category. Methods: The bio-behavioral survey of MSW in Nairobi, Kenya, utilized respondent-driven sampling to recruit MSW. Structured interviews captured MSW's behavioral aspects, and biological tests for HIV and other sexually transmitted infections (STIs) were done. Results: Analysis of the two age categories, 18 – 24 years (younger MSW) and 25 years and above (older MSW), shows that of all the participants, a significantly higher proportion of younger MSW (59.6% crude, 69.6% RDS-adjusted) were recruited compared to older MSW(40.4% crude, 30.4% RDS-adjusted, P< 0.001). Young male sex workers were more likely to report multiple sexual partnerships in the last 12 months and had multiple receptive anal intercourses (RAI) acts in the last 30 days than older MSW: 0-2 RAI acts (20.6% versus 8.6%, P=0.0300), 3-5 RAI acts (26.3 versus 11.5, P < 0.001), and >5 RAI acts (26.3% versus 11.5%, P < 0.01). Furthermore, younger MSW's were significantly more likely to have 3-5 insertive anal intercourse (IAI) with a regular male sex partner in the last 30 days than older MSW (24.3% versus 8.0%, P < 0.01). Younger MSW were more likely to report other STIs (28.5% (95% CI : 19.1% – 40.4%) than older MSW (19.0% (95% CI : 7.7% – 29.2%). However, older MSWs were more likely to be infected with HIV (32.3% versus 9.9 %, P< 0.01). Conclusions: Owing to the HIV and STI risks among the two age bands, intensified and targeted efforts are needed on risk reduction campaigns and expanded access to services.